1997
DOI: 10.1161/01.cir.95.3.684
|View full text |Cite
|
Sign up to set email alerts
|

Complement C5a, TGF-β1, and MCP-1, in Sequence, Induce Migration of Monocytes Into Ischemic Canine Myocardium Within the First One to Five Hours After Reperfusion

Abstract: Beginning in the first 60 minutes after reperfusion, C5a, TGF-beta 1, and MCP-1, acting sequentially, promote infiltration of monocytes into formerly ischemic myocardium. These events may promote the healing of myocardial injury facilitated by reperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
159
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 200 publications
(166 citation statements)
references
References 37 publications
5
159
0
1
Order By: Relevance
“…Recent investigations using experimental models of myocardial infarction demonstrated strong induction of several members of the chemokine family in the ischemic heart supporting their role in leukocyte recruitment [32], infarct angiogenesis and fibrous tissue deposition [96].…”
Section: The Chemokine Family In Myocardial Infarctionmentioning
confidence: 98%
See 2 more Smart Citations
“…Recent investigations using experimental models of myocardial infarction demonstrated strong induction of several members of the chemokine family in the ischemic heart supporting their role in leukocyte recruitment [32], infarct angiogenesis and fibrous tissue deposition [96].…”
Section: The Chemokine Family In Myocardial Infarctionmentioning
confidence: 98%
“…Complement activation may play an important role in mediating neutrophil and monocyte recruitment in the injured myocardium [31]. The contribution of complement activation in mononuclear cell recruitment appears to be particularly important during the first hour of reperfusion [32].…”
Section: The Complement Cascadementioning
confidence: 99%
See 1 more Smart Citation
“…Reperfusion after ischemia can salvage the ischemic myocardium, however, simultaneously it causes additional cell death and attenuates the beneficial effects of reperfusion itself, called myocardial ischemia/reperfusion (I/R) injury [2]. Inflammation has been shown to play a critical role in the pathophysiology of myocardial I/R injury [3], and various immune cells, such as neutrophils, T lymphocytes, monocytes/macrophages, and mast cells, are involved in myocardial I/R injury [4][5][6][7]. Recent study by Yang et al demonstrated that CD4 + T lymphocytes played an important role in the development of I/R injury and interferon (IFN)-γ was involved in their action by using Rag1 knockout mice lacking mature lymphocytes [5].…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Early reperfusion of the ischemic myocardium is a key clinical intervention after myocardial infarction and is attended by a robust inflammatory reaction involving both neutrophils and mononuclear cells. 5,6 It has been shown that late reperfusion, when myocardial salvage is no longer possible, improves myocardial repair and obviates infarct expansion. …”
mentioning
confidence: 99%